Effects of dietary pretreated Chinese herbal medicine supplementation on production performance, egg quality, uterine histopathological changes, and antioxidant capacity in late-phase laying hens - Yu, Ao-Chuan; Wang, Min-An; Chen, Li; Long, Cheng; Guo, Yong; Sheng, Xi-Hui; Wang, Xiang-Guo; Xing, Kai; Xiao, Long-Fei; Ni, He-Min; Li, Jian-Tao; Qi, Xiao-Long (Frontiers in Physiology, 2023)
The study aimed to evaluate the effects of pretreated Chinese herbal medicine (PCHM) on egg quality, production performance, histopathological changes in the uterus, antioxidant capacity, and antioxidant gene expression in late-phase layers. Jinghong No.1 layers (n = 360, 68 weeks old) were assigned randomly to one of four dietary interventions. Each treatment was replicated six times. Repeat 15 chickens per group. All birds were fed a diet composed of a corn-soybean meal-based diet supplemented with 0, 0.2, 0.4, or 0.8% PCHM for 6 weeks. Dietary PCHM supplementation had no significant effects on laying rate, feed consumption, yolk color, and shape index. With increasing PCHM level the Haugh unit linearly increased (P < 0.05). Supplementation of 0.8% PCHM increased egg weight, compared with the control (P < 0.05). PCHM can effectively alleviated the pathological changes caused by aging in the uterus including hemorrhage, and many inflammatory cell infiltrations. Supplementation of 0.4% PCHM increased glutathione peroxidase (GSH Px) in liver, magnum, and plasm considerably, compared with the control (P < 0.05). Supplementation of PCHM decrease in the liver, magnum, and uterus on malondialdehyde (MDA) content, compared with the control (P < 0.05). Compared with the control group, mRNA expressions of glutathione peroxidase 1 (GPX1), peroxidase 4 (GPX4), catalase (CAT), and nuclear factor E2-related factor 2 (Nrf2) in the magnum, liver, and uterus were dramatically rose in the 0.4% PCHM supplementation group (P < 0.05). In summary, dietary supplementation after PCHM increased egg weight and quality in late-phase laying hens. Dietary PCHM increased the antioxidative capacity of late-phase laying hens, which could be associated with increased mRNA expression of antioxidant enzymes and Nrf2. These findings provide potential for using PCHM to increase the production performance in late-phase laying hens.